PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN RITEL KOTA SEMARANG - Rudolfcahyo, Rudolfcahyo; Agustina, Menik Tetha (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Behind the rapid development of business competition in the retail industry in a major city, there is a need to improve the quality and capabilities of the workforce in order to enhance employee performance. This study aims to deeply analyze the effect of work stress on employee performance in Semarang City. Using a quantitative approach with a causal design, the study involved 79 employee respondents from various retail stores in Semarang as a sample through random sampling techniques. Data were collected using a Likert-scale questionnaire and analyzed through a series of statistical tests, including validity, reliability, normality, Product Moment correlation, and simple linear regression. The research results indicate that work stress has a significant positive effect on employee performance, marked by a correlation coefficient of 0.511. Hard skill training and employee performance, marked by a correlation coefficient of 0.507. Furthermore, work stress is proven to contribute 26.1% to variations in employee performance, with model significance test results confirming a real effect (p = 0.000), where an increase in stress levels tends to enhance productivity and service quality. Based on these findings, store management is advised to develop stress management strategies that align with field demands and local work culture to maintain high employee performance sustainably. ABSTRAK Di balik pesatnya perkembangan persaingan bisnis industri ritel disuatu kota besar, perlu adanya peningkatan mutu dan kemampuan tenaga kerja guna meningkatkatkan kinerja karyawan. Penelitian ini bertujuan untuk menganalisis secara mendalam pengaruh stres kerja terhadap kinerja karyawan Kota Semarang. Menggunakan pendekatan Kuantitatif dengan desain Kausalitas, penelitian melibatkan 79 responden karyawan dari berbagai toko ritel di kota Semarang sebagai sampel melalui teknik random sampling. Data dikumpulkan menggunakan kuesioner berskala Likert dan dianalisis melalui serangkaian uji statistik, termasuk validitas, reliabilitas, normalitas, korelasi Product Moment, serta regresi linier sederhana. Hasil penelitian menunjukkan bahwa stres kerja memiliki pengaruh positif yang signifikan terhadap kinerja karyawan ditandai dengan koefisien korelasi sebesar 0,511. pelatihan hardskill dan kinerja karyawan, ditandai dengan koefisien korelasi sebesar 0,507. Lebih lanjut, stres kerja terbukti memberikan kontribusi sebesar 26,1% terhadap variasi kinerja karyawan, dengan hasil uji signifikansi model yang mengonfirmasi pengaruh nyata (p= 0,000) di mana peningkatan tingkat stres cenderung meningkatkan produktivitas dan kualitas pelayanan. Berdasarkan temuan ini, manajemen toko disarankan menyusun strategi pengelolaan stres yang selaras dengan tuntutan lapangan dan budaya kerja lokal agar performa karyawan tetap tinggi secara berkesinambungan.